Recommendations on multidisciplinary management of elective surgery in people with haemophilia. Issue 5 (26th June 2018) - Escobar, M. A.; Brewer, A.; Caviglia, H.; Forsyth, A.; Jimenez‐Yuste, V.; Laudenbach, L.; Lobet, S.; McLaughlin, P.; Oyesiku, J. O. O.; Rodriguez‐Merchan, E. C.; Shapiro, A.; Solimeno, L. P.
Abstract : Planning and undertaking elective surgery in people with haemophilia (PWH) is most effective with the involvement of a specialist and experienced multidisciplinary team (MDT) at a haemophilia treatment centre. However, despite extensive best practice guidelines for surgery in PWH, there may exist a gap between guidelines and practical application. For this consensus review, an expert multidisciplinary panel comprising surgeons, haematologists, nurses, physiotherapists and a dental expert was assembled to develop practical approaches to implement the principles of multidisciplinary management of elective surgery for PWH. Careful preoperative planning is paramount for successful elective surgery, including dental examinations, physical assessment and prehabilitation, laboratory testing and the development of haemostasis and pain management plans. A coordinator may be appointed from the MDT to ensure that critical tasks are performed and milestones met to enable surgery to proceed. At all stages, the patient and their parent/caregiver, where appropriate, should be consulted to ensure that their expectations and functional goals are realistic and can be achieved. The planning phase should ensure that surgery proceeds without incident, but the surgical team should be ready to handle unanticipated events. Similarly, the broader MDT must be made aware of events in surgery that may require postoperative plans to be changed. Postoperative rehabilitation should begin soon after surgery, with attention paid to management of haemostasis and pain. Surgery in patients with inhibitors requires even more careful preparation and should only be undertaken by an MDT experienced in this area, at a specialized haemophilia treatment centre with a comprehensive care model.